Gut Microbiota Shapes the Efficiency of Cancer Therapy - Ma, Weidong; Mao, Qixing; Xia, Wenjie; Dong, Gaochao; Yu, Changhua; Jiang, Feng (Frontiers in Microbiology, 2019)
Summary: The homeostasis of gut microbiome is linked with the balance of host immune system. Increasing evidence showed that cancer therapy would perturb the host immune response and result dysbiosis of immune system, which influenced the efficiency of the therapy. The gut microbes play increasingly significant role in the cancer therapy with the deepening of the research, which modulate the drug efficacy, abolish the anti-cancer effect, and mediate the toxicity. The systems biology provides an opportunity to discover of the important role the gut microbiota playing in almost all aspects of human health. The existed evidence provokes a hypothesis that gut microbiota is closely related to the pharmacological effects of chemical therapy and novel targeted immunotherapy. Gut microbiota shapes the efficiency of the drugs through several key mechanisms (metabolism, immunomodulation, translocation, enzymatic degradation, reduction of diversity and ecological variability). Therefore, the gut microbiota emerges as a novel target to enhance the efficacy and reduce the toxicity and adverse effect of cancer therapy. In this review, we outlined the role of gut microbiota in modulating cancer therapy and the implication in improving the efficacy of chemotherapy and immunotherapy in clinical practice. We also summarized the current situation that the limitations to the safety and effectiveness of probiotics in cancer therapy in personalized cancer therapy.